CHALLENGES AND STRATEGIES IN TRANSLATING NON-EQUIVALENT LEXICAL UNITS IN ENGLISH-UZBEK BILINGUAL DICTIONARIES (Лучшие интеллектуальные исследования, 2025)
Abstract. Interpreting culture-specific words, expressions, and authentic terms between English and Uzbek postures noteworthy etymological and social challenges due to contrasts in conventions, social structures, and verifiable foundations. Numerous words and expressions need coordinate reciprocals, requiring interpreters to embrace different procedures to protect meaning whereas guaranteeing comprehension. This ponder looks at the troubles of interpreting such terms and investigates successful interpretation techniques, counting clear interpretation, borrowing, and relevant clarification. By analyzing particular illustrations, this investigate highlights how interpreters explore cultural and phonetic crevices to preserve the keenness of the first text. The discoveries recommend that a combination of interpretation strategies is fundamental to realize exactness and social pertinence, eventually moving forward bilingual word references and scholarly interpretations.